MEDIATION IN BRAZIL: A WAY FOR THE SOLUTION OF PATIENT-MEDICAL CONFLICTS - Melo, Vivianne Rodrigues; Oliveira, Caroline Buarque Leite (PEOPLE: International Journal of Social Sciences, 2019)
The problem of excessive litigation in Brazil is a reality that compromises the management of the Judiciary. The lawsuits brought by patients against doctors, involving medical malpractice in the provision of health services, fit the reported procedural delay critic panorama. In order to verify the efficacy of an substitute method for the judicialization of the doctor-patient relationship, the research aims to analyze the feasibility of judicial or extrajudicial mediation as alternative medicine judicialization in Brazil. For this study, It was adopted a deductive and theoretical methodological, the analysis of legislation and documentation, as well as the bibliographic survey; the qualitative data presented were collected from documentary sources statistics. The investigation results confirm the mediation as a useful strategy for solution for the self-composition of conflicts involving patients and doctors, in order to preserve access to justice and the social pacification. Concludes that the judicial or extrajudicial mediation constitutes an environment that enables dialogue and interaction of the parties involved and effectiveness of civil procedure post-modern. The learning flows in future work, with the aim of studying the papers of the patient, the doctor and the mediator by optical the theory psychoanalytic.